Untargeted metabolomics of fermented onion (Allium cepa L) using UHPLC Q-TOF MS/MS reveals anti-obesity metabolites and in vivo efficacy in Caenorhabditis elegans. (15th March 2023) - Barathikannan, Kaliyan; Chelliah, Ramachandran; Yeon, Su-Jung; Tyagi, Akanksha; Elahi, Fazle; Vijayalakshmi, Selvakumar; Agastian, Paul; Arockiasami, Vijayakumar; Hawn Oh, Deog
Graphical abstract: Highlights: FOE inhibited pancreatic lipase 89.5 ± 1.25 % potentially than ROE (33.4 ± 0.86 %). Compared to ROE, the examined FOE exhibited superior antioxidant properties. UHPLC Q-TOF MS/MS detected major bioactive compounds foranti-obesity effectively. FOE and quercetin enhanced the C. elegans lifespan and reduced lipids. Abstract: The bioconversion of onion extracts with P. acidilactici MNL5 enhances the metabolites and has a synergistic lipid-reduction impact that is beneficial for anti-obesity studies. The 48 h fermented onion extracts (FOE) demonstrated an enhanced inhibitory activity against pancreatic lipase (89.5 ± 1.25 %) as compared to the raw onion extract (ROE) (33.4 ± 0.86 %). The antioxidant properties of FOE significantly increased compared to the ROE inhibitory effect on DPPH (99.5 ± 2.40 mg vitamin C equiv./mg, DW FOE), and ABTS (104.5 ± 2.32 mg vitamin C equiv./mg, DW FOE). Based on FOE's higher antioxidant activity, UHPLC-Q-TOF-MS/MS demonstrated dramatic changes in the untargeted metabolite profile as compared to ROE. Moreover, C. elegans supplemented with FOE and quercetin exhibited an enhanced lifespan activity, lipid reduction, and decreased triglycerides. FOE can lower cholesterol and enhance quercetin to promote pancreatic lipase activity for synergistic anti-obesity effects.